THE REALIST PARADIGM OF ENERGY DIPLOMACY IN THE RUSSIAN SCIENTIFIC TRADITION AND ITS PRACTICAL APPLICABILITY - R. О. Reinhardt; S. V. Pronichkin (Vestnik MGIMO-Universiteta, 2018)
Nowadays energy diplomacy tends to be one of most relevant and important fields of applied research in International Relations. It is characterized by an interdisciplinary approach being an intersection of political and economic theory, international law, energetics, theory of diplomacy, as well as other fields. Still, numerous research works in the given area both in Russia and abroad are characterized by a number of controversies, such as absence of a common theoretical, methodological basis and conventional terminology, as well as lack of consistency in the choice of scientific paradigms, which leads to divergence of research results and hinders the comparability of the latter. Along with that, in terms of scientific policy it is worth mentioning the absence of a common scientific space in the above field of research, which tends to be shaped by national research cultures and traditions. Throughout the 2000-2010s representatives of the MGIMO scientific school have accumulated experience in dealing with problems of energy diplomacy. However, most of the existing works do not specify the selected political theory paradigms, such as, for instance, realism, liberalism or constructivism. With no intention to conduct a comparative analysis of the aforementioned concepts, the authors of the article outline the key theoretical findings of political realism as the most suitable paradigm for explaining, analyzing and eventually forecasting the recent trends and phenomena given the current geopolitical and economical juncture. They prove the applicability of the proposed model to the OPEC case study and demonstrate its potential practical usefulness for policy-makers in foreign affairs and international energy relations.